Analysis of Mathematical Problem Solving Ability of Junior High School Students Based on Polya's Stages in View of Math Anxiety Levels - Lutfiah, Ulfa; Yarman, Yarman; Fauzan, Ahmad; Jamaan, Elita Zusti (STKIP Singkawang, 2025)
This study aims to describe mathematics anxiety, the factors that cause it, and the mathematical problem solving ability of junior high school students based on Polya's stages and the level of mathematics anxiety. Using a case study approach with qualitative methods, the research involved 66 eighth-grade students at SMP Negeri 24 Padang, with 14 selected as subjects representing low, moderate, and high levels of anxiety. The instruments used include math anxiety questionnaire, math problem solving test, and interviews. The results showed that: (1) 68.2% of students experience moderate anxiety, 18.2% low, and 13.6% high; (2) Students' math anxiety is due to difficulty understanding formulas, exam pressure, and low self-confidence and doubts about abilities which affect motivation and performance; (3) Students' abilities at Polya’s stages vary, with 61% able to understand the problem, 44% able to devise a plan, 8% able to carry out the plan, and 6% able to look back; (4) Students with low math anxiety able to follow all stages of Polya. Cognitively they are able to strategize logically, somatically there is no physical disturbance, and attitudinally they show high self-confidence; (5) Students with moderate anxiety show variations in ability. They understand the problem, but procedural errors often occur. Somatic symptoms such as tension disrupt focus, and attitudinally appear hesitant and lack confidence; (6) Students with high anxiety are only able to understand the problem. Their cognition is limited, somatic symptoms such as trembling, and attitudinally they tend to be afraid of failure and reluctant to try.